From news article to social media post: A quantitative and qualitative analysis of news outlets' social media logic. - Disseldorp, Jorge; Bouko, Catherine (Atlantic Journal of Communication)
The digital spaces that news consumers encounter news in can directly affect how important societal events are consumed. News distribution and consumption habits are especially increasingly shaped by Social Networking Sites (SNSs). To foster engagement online, newsrooms may opt to cater their content to their social media profiles by highlighting story elements that they believe appeal to audiences on SNSs. The Social Media Logic (SML) which underlies the remediation of news articles to news posts is the subject of this study. It proposes a framework based on syntactic theory to comprehensively identify the text segments that are affected by these transformations. The paper presents a study in which approximately 700 Facebook posts and 700 articles are compared to each other to assess how editorial changes affect news presentation on Facebook. It finds that remediations tend to impact the rhetoric force with which events are presented. These edits do not necessarily exhibit a clear sense of directionality, as linked to an intensified or weakened expression of news values on social media and a clear editorial strategy. On SNSs where outlets are forced to compete for attention, conciseness takes on a more principal role over a complete overhaul of traditional news values.